2011
DOI: 10.1111/j.1365-2958.2011.07714.x
|View full text |Cite
|
Sign up to set email alerts
|

Role for Sit4p‐dependent mitochondrial dysfunction in mediating the shortened chronological lifespan and oxidative stress sensitivity of Isc1p‐deficient cells

Abstract: Summary Saccharomyces cerevisiae cells lacking Isc1p, an orthologue of mammalian neutral sphingomyelinase 2, display a shortened lifespan and an increased sensitivity to oxidative stress. A lipidomic analysis revealed specific changes in sphingolipids that accompanied the premature aging of Isc1p deficient cells under severe calorie restriction conditions, including a decrease of dihydrosphingosine levels and an increase of dihydro-C26-ceramide and phyto-C26-ceramide levels, the latter raising the possibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 47 publications
7
72
0
Order By: Relevance
“…Consistently, the deletion of TOR1, SCH9, SIT4 or HOG1 suppresses mitochondrial fragmentation [26-28; this study], which in turn is associated with improvement of the organelle function, as shown by our lab [26][27][28], and lowers the induction of mitophagy in isc1Δ cells under respiratory conditions (in lactate medium, this study). Since mitochondrial fragmentation is a critical step for the sequestration of dysfunctional mitochondrial by autophagosomes [38] and oxidative stress is a signal for mitophagy induction [39], it seems that the suppression of mitochondrial fragmentation and reduction of ROS levels [26-28; this study] in isc1Δtor1Δ, isc1 Δsch9Δ, isc1Δsit4Δ and isc1Δhog1Δ cells lead to the attenuation of mitophagy.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Consistently, the deletion of TOR1, SCH9, SIT4 or HOG1 suppresses mitochondrial fragmentation [26-28; this study], which in turn is associated with improvement of the organelle function, as shown by our lab [26][27][28], and lowers the induction of mitophagy in isc1Δ cells under respiratory conditions (in lactate medium, this study). Since mitochondrial fragmentation is a critical step for the sequestration of dysfunctional mitochondrial by autophagosomes [38] and oxidative stress is a signal for mitophagy induction [39], it seems that the suppression of mitochondrial fragmentation and reduction of ROS levels [26-28; this study] in isc1Δtor1Δ, isc1 Δsch9Δ, isc1Δsit4Δ and isc1Δhog1Δ cells lead to the attenuation of mitophagy.…”
Section: Discussionsupporting
confidence: 71%
“…Importantly, this was correlated with loss of cell viability in isc1Δ cells (Fig. 1C), as previously described [26]. We also analysed total levels of Por1p, a mitochondrial outer membrane protein, as a means to monitor mitochondrial turnover during ageing.…”
Section: Mitophagy Is Hyperactivated In Isc1p-deficient Cellsmentioning
confidence: 82%
See 3 more Smart Citations